THE POLITICAL POTENTIAL OF MONEY IN REGIONAL ELECTIONS THAT TAKE PLACE IN THE PERSPECTIVE OF LAW NUMBER 6 OF 2O2O CONCERNING THE ELECTION OF GOVERNORS, REGENTS, AND MAYORS - Herling Walangitang (Jurnal Scientia, 2023)
Politics and democracy are two important pillars in holding general elections for regional heads within the constitutional system for development purposes in the Unitary State of the Republic of Indonesia. Pilkada is very closely related to the rights of civilians to exercise their political rights in electing regional heads who are considered capable of developing their regions in various aspects of life. Regarding the handling of the spread of the Corona Virus Covid-19 which has become a national disaster, it is urgent to make extra ordinary policies and steps in every region that will hold an election, as well as if it is deemed necessary to postpone the stages of the election for the governor and deputy governor, regent and deputy regent. , as well as the mayor and deputy mayor simultaneously so that it can still be implemented in a democratic and quality manner but can still maintain domestic political stability;